PEREMPUAN SEBAGAI PENDAMPING SEPADAN BAGI LAKI-LAKI DALAM KONTEKS ALKITAB DAN BUDAYA BATAK - Herowati Sitorus (Jurnal Teologi Cultivation, 2019)
AbstractThis research is library research. The purpose of this study is to determine the role of woman as an equal companion for man in the context of the Bible and Batak’s culture. Human are not created by differences in their statu. They are made equal by God. God created the woman from the rib of the man (Gen. 2:23) which means a woman be a companion of the man and be a friend in their family or the wider community. Therefore, in this era many man and woman are not aware of their existence.Keywords: Commensurate Companion, Human